Percepção dos gestores escolares sobre a utilização da caminhada para acesso à escola - Onishi, Viviane Leão da Silva (2016)
Brazil's cities in recent decades have a predominance of car use as children's mode of transport to school. In carrying out the route home-school by motorized modes children practice less physical activity to the detriment of health. Policies developed in schools can play an important role in determining how students travel to school. In this context, this research aims to identify the factors that influence the perception of managers about using the walk to access the school. The focuses of the research are the municipal and private elementary schools 1. The case study was conducted in the city of São José do Rio Preto. Data collection was carried out with the school managers (directors, coordinators and teachers) through questionnaires on travel behavior of the students, information on any activities at school to teach students to behave in traffic, opinions of management on the relationship between physical activity and health of children, children's ability to to walk to school, the barriers surrounding the school and attitude of managers regarding the use of different modes of transport and the impact of vehicle traffic in urban . The results showed that the estimation of directors and coordinators on the modes of transport used by students does not differ from a survey conducted by teachers significantly, and in private schools motorized individual transport is the most used by students and public schools over half of students walk or use public transportation to school. It was found that the traffic behavior on teaching is applied in all schools, although the directors and coordinators are more likely to say that the activities are carried out in your school. The school managers have a positive perception of the importance of physical activity, with acceptance rates above 90%. There is no consensus about the best age and abilities of children to make safe decisions alone and analysis on the perception of managers of barriers around the schools that may hinder access to foot it was found that about half of the managers have positive about the quality of the environment around the schools, but other managers have indifferent opinion about the quality of the environment. Regarding the use of different modes of transport it was observed that attitudes regarding the use of buses are in general negative, more than half of managers are indifferent to automobile use and favorable to the use of the walk. In the manager's attitude regarding the impact of vehicle traffic in urban areas the vast majority of managers are concerned about the impact of traffic on the environment. Perceptions regarding the active mobility should be worked through school policies to improve students' skills as pedestrians and through public policies to improve the environment in the school environment and encourage the use of active modes of transportation.